Dancehall and hip-hop : youth perceptions of sexuality and violence - Jackman, W. Marc (2010)
Attempts to assess the impact of dancehall and hip-hop music on the behaviour and perceptions of adolescent and youth. Seeks to specifically determine the extent to which Trinidadian adolescents endorse dancehall and hip-hop music as favourites and the consequences of such endorsements - in particular, sexuality and violent perceptions and behaviours.\n